Waterfront blues : labour strife at the Port of Montreal, 1960-1978 - Pathy, Alexander C. (Book collections on Project MUSE., 2004)
Waterfront Blues is the story of the dramatic events surrounding the labour battles at the Port of Montreal in the 1960s and 70s. During that time, the prospect and reality of technological change poisoned labour relations, provoking a series of bitter strikes as well as repeated exercises in government intervention. It was not until 1978 that management and labour were able to negotiate a collective agreement without a work stoppage or government intervention. In this new study, Alexander Pathy probes deeply into the causes of this labour unrest and charts the efforts made by the parties concerned - management, labour, and government to resolve the crisis. It draws upon the author's own experiences as a management representative and key figure at the Port of Montreal, as well as extensive research into the records generated by all the parties involved. Exploring complicated issues of labour relations clearly and concisely, Waterfront Blues also boasts a fascinating cast of characters, including the colourful labour minister Bryce Mackasey; the shrewd shipping industry lawyer and future prime minister Brian Mulroney; the decisive and no-nonsense management spokesperson Arnie Masters; the fiery union leader Jean-Marc St-Onge; and the blunt, brutally effective mediator/arbitrator Judge Alan B. Gold.